Effect of Alcaligenes faecalis inoculation in different casing mixtures on its physico-chemical properties and yield stimulation of Agaricus bisporus - ., Neelam; Upadhyay, Vinod; Kushwaha, KP S (Mushroom Research, 2016)
Experiment was conducted to study physico-chemical properties viz., bulk density, pH and electrical conductivity (E.C) and yield performance of Agaricus bisporus using different casing materials i.e. Farm yard manure (FYM), spent compost (SC) and coir pith (CP) inoculated with broth culture of Alcaligenes faecalis. It was found that bulk density of casing mixture ranges from 0.61 to 0.72 gm/cm and was slightly increased with inoculation of bacterium in most of the cases except CP+SC+ A. faecalis. The pH of casing soils varied from 6.23 to 6.7. The highest E.C (2.08 deciâ€“ simen 3 ) was found in FYM + SC + A. faecalis whereas lowest E.C (1.14 deciâ€“ simen -1 -1 ) was observed in CP + SC, however, electrical conductivity slightly increased with inoculation of bacterium in all the cases. Enhanced yield was obtained from all the four casing materials by mixing the bacterium A. faecalis. The casing soil treatment with FYM + SC + A. faecalis gave the highest yield (21.27 kg/Qtl compost).Â